Trappings of femininity: A test of the "beauty as currency" hypothesis in shaping college women's gender activism. (June 2017) - Calogero, Rachel M.; Tylka, Tracy L.; Donnelly, Lois C.; McGetrick, Amber; Leger, Andrea Medrano
Highlights: We tested the beauty as currency hypothesis in college women. Beauty as currency belief was directly and positively linked to self-objectification. Beauty as currency belief was directly and positively linked to support for the gender status quo. Beauty as currency belief was indirectly and negatively linked to gender activism. Results highlight role of beauty ideology in women's political consciousness. Abstract: This study investigated whether believing beauty is a primary currency for women operates as an antecedent force in the relation between self-objectification and gender activism. Ninety-four ethnically diverse women attending a small liberal arts college in the southeastern United States completed the study questionnaires online for course credit. Preliminary results demonstrated beauty as currency belief, self-objectification, and support for the gender status quo were negatively associated with gender activism. A serial mediation analysis revealed support for the proposed model: Beauty as currency belief was indirectly and inversely linked to gender activism through self-objectification and support for the gender status quo, offering initial evidence for our beauty as currency hypothesis. These findings suggest belief in the notion women will reap more benefits from their bodies than other attributes or pursuits may be an important legitimizing feature of feminine beauty ideology that works through self-objectification against gender social change.